The MacArthur Highway & other relics of American empire in the Philippines - McCallus, Joseph P. (Potomac Books, 2010)
It has been more than a century since the American conquest and subsequent annexation of the Philippines. Although the nation was given its independence in 1946, American cultural authority remains. This title retraces the route Gen Douglas MacArthur took during his liberation of the country in 1944-45.